Balance function and sensory integration after mild traumatic brain injury. (January 2015) - Lin, Li-Fong; Liou, Tsan-Hon; Hu, Chaur-Jong; Ma, Hon-Ping; Ou, Ju-Chi; Chiang, Yung-Hsiao; Chiu, Wen-Ta; Tsai, Shin-Han; Chu, Woei-Chyn
Abstract Objective: This study examined the disparities in balance functions and sensory integration in patients with mild traumatic brain injuries (mTBIs) and healthy controls. Participants: One hundred and seven patients with mTBI and 107 age- and sex-matched controls were recruaited for this study. Primary measures: Symptoms of dizziness, balance functions and the ability to perform daily activities were assessed using the dizziness handicap inventory (DHI). This study also performed the postural-stability test and a modified clinical test of sensory integration by using the Biodex Stability System (BBS). Results: DHI scores (functional, emotional, physical and total self-reported scores) were substantially increased in patients following an mTBI compared with the scores of the controls (p < 0.000). The postural-stability test indices (anterior-posterior) (p = 0.045) and the sensory-integration test index (eyes-open-firm-surface index) (p = 0.006) were substantially lower in patients with mTBI than in the controls. However, indices of two other postural-stability test indices (overall and medial-lateral) and three other sensory-integration tests indices (eyes-closed-firm-surface, eyes-open-foam-surface and eyes-closed-foam-surface) measured for the mTBI group did not differ from those of the control group. Conclusion: Activities of daily living, balance in postural stability and sensory integration were strongly impaired in patients with mTBI.